Spenders and Tightwads Among Newlyweds: Perceptions of Partner Financial Behaviors and Relational Well-Being - Heather H. Kelley; Alexa B. Chandler; Ashley B. LeBaron-Black; Xiaomin Li; Melissa A. Curran; Jeremy B. Yorgason; Spencer James (Journal of Financial Therapy, 2022)
Finances, and how couples manage their finances, can have important implications for couples’ relational well-being. Using data from 1,585 couples that participated in the CREATE study (a nationally representative dyadic dataset of U.S. newlywed couples), we examined how perceiving one’s spouse as a financial spender (i.e., spending more than they ideally would) or financial tightwad (i.e., spending less than they ideally would) was associated with several measures of relational well-being (i.e., satisfaction, commitment, and power) through actor-partner interdependence structural equation models. Results showed that perceiving one’s partner as a spender was detrimental for both the individual’s and the partner’s marital satisfaction, marital commitment, and marital power. Perceiving one’s partner as a tightwad was detrimental for both the individual’s and the partner’s marital commitment and marital power. The findings suggest that interventions focused on perceptions of financial management behaviors may help strengthen relational well-being among newlyweds.
Keywords: financial management; relational well-being; spenders; tightwads; newlywed